Enhanced Anticancer Efficacy of Chemotherapy by Amphiphilic Y-Shaped Polypeptide Micelles - Hua, Cong; Zhang, Yi; Liu, Yuanhao (Frontiers in Bioengineering and Biotechnology, 2021)
Although the treatment modalities of cancers are developing rapidly, chemotherapy is still the primary treatment strategy for most solid cancers. The progress in nanotechnology provides an opportunity to upregulate the tumor suppression efficacy and decreases the systemic toxicities. As a promising nanoplatform, the polymer micelles are fascinating nanocarriers for the encapsulation and delivery of chemotherapeutic agents. The chemical and physical properties of amphiphilic co-polymers could significantly regulate the performances of the micellar self-assembly and affect the behaviors of controlled release of drugs. Herein, two amphiphilic Y-shaped polypeptides are prepared by the ring-opening polymerization of cyclic monomer L-leucine N-carboxyanhydride (L-Leu NCA) initiated by a dual-amino-ended macroinitiator poly(ethylene glycol) (mPEG-(NH2)2). The block co-polypeptides with PLeu8 and PLeu16 segments could form spontaneously into micelles in an aqueous solution with hydrodynamic radii of 80.0 ± 6.0 and 69.1 ± 4.8 nm, respectively. The developed doxorubicin (DOX)-loaded micelles could release the payload in a sustained pattern and inhibit the growth of xenografted human HepG2 hepatocellular carcinoma with decreased systemic toxicity. The results demonstrated the great potential of polypeptide micellar formulations in cancer therapy clinically.